THE RELATIONSHIP BETWEEN PERSONALITY TRAITS, RELATIONSHIP QUALITY AND CONFLICT MANAGEMENT STYLES AMONG EMPLOYEES DURING PANDEMIC: A CONCEPTUAL PAPER - Nor Hidayatun Abdul Razak; Khadijah Athirah Mohamad Shamshudin; Shaiful Azlan Abdul (International Journal of Accounting, Finance and Business, 2022)
This research will investigate the relationship between personality traits, relationship quality, and conflict management style among employees during the pandemic. Based on the conflict management style, the researcher specifically expected that integrating, obliging, compromising, dominating, and avoiding styles would be related to extraversion, openness to experience, agreeableness, conscientiousness, and neuroticism, which are the fivefactor model of personality traits as well as the relationship quality. Thus, the present conceptual paper discussed how relationship quality mediated the relationship between personality traits and conflict management style. Ultimately, a conceptual framework is developed based on the reviewed literature.